Literature and Politics : the representation of the African postcolonial elites in Chinua Achebe and Pepetela - (:unkn) unknown (My University, 2012)
This dissertation presents a critical and comparative study of the novels entitled No Longer at Ease (1960) and A man of the People 1966), by the Nigerian writer Chinua Achebe, and the novels A geração da utopia (1992) and Predadores (2005), by the Angolan writer Pepetela. By means of the analysis of historical, geographical, political and literary contexts that surround and permeate the fabric of the novels mentioned above, we demonstrate how both African writers appropriate the novel – a cosmopolitan genre par excellence – to adapt it to local conditions of novel production in postcolonial Africa, so to literarily express the (mis)match between metropolis and postcolony and the process of (re)construction of the new nation. What interests us in these novels is to reflect on the types of negotiations and concessions that the narrators need to do to tell their stories. To do so, we study the status of the narrator, the configuration of the characters, the transformation of the social process in literary form, the representation of the nation and the language summoned by the authors to represent such reality. We focus primarily on the characters that represent the new “bourgeois” of the postcolonial periods in Nigeria and Angola, who belong to these new social class, responsible for the burocratic domain which emerges in African countries after the processes for independence in the 60’s. We chose Pepetela to dialogue with Achebe because they have similar literary style and because their thematic choices are very similar. Both are keen observers of their countries’ realities and they use sharp language, full of subtle irony. Thus, we propose to investigate the thesis that there is an articulation between the theme of the rising of corrupted characters, members of new bourgeois elites, and the progressive modifications in the narratives analysed, as we move from the reading of novels which enact moments previous to the independences, to the
Keywords: African Research